Detection of Deception through Mental Verbs in the Interview of Murder Suspect Kumala Wongsu in the Kopi Sianda Case (A Forensic Linguistics Study) - Sarmila Bambang; Dakia N. Djou; Asna NTelu (Universitas Islam Negeri Palopo, 2026)
This study aims to describe the use of mental verbs and the forms of deception found in the utterances of Jessica Kumala Wongso in the cyanide coffee case through a forensic linguistics approach. This research employed a descriptive qualitative method with a pragmatic approach. The data consisted of Jessica Kumala Wongso’s verbal utterances obtained from television interviews, documentaries, and digital media related to the cyanide coffee case. The data were collected through observation, transcription, reading, and note-taking techniques. The analysis was conducted by identifying, classifying, and interpreting mental verbs as well as forms of deception based on Paul Ekman’s theory of deception. The findings revealed four types of mental verbs used in the utterances, namely affective, perceptive, cognitive, and desiderative mental verbs. Among these types, affective and cognitive mental verbs were the most dominant. The use of affective mental verbs reflected emotional emphasis and attempts to build a particular psychological image, while cognitive mental verbs indicated uncertainty, hesitation, and the reduction of responsibility toward the information conveyed. In addition, the study identified five forms of deception, namely direct lie, concealment, evasion, strategic deception, and false belief. The most dominant forms of deception were concealment and evasion, which were realized through indirect statements, uncertainty expressions, and avoidance strategies. The findings indicate that mental verbs can function as linguistic indicators in detecting deception within legal communication. This study contributes to the development of forensic linguistics, particularly in analyzing language as an indicator of deception in interviews and legal investigations